Baderneiros, artistas e sonhadores: contaminações da cultura em corposmídia que dançam - Dini, Daniela (2019)
This master thesis aims to study the power of interlocutions and the exchange and “contagious nets” that exist between popular cultures and contemporary performances. To discuss the empiric corpus of the choreographer Luis Ferron’s work and his way of using the iconography of a Brazilian ideology without fixing preestablished or framed cultural elements. This research suggests that the “contagious net” tested by this choreographer may be a device able of provoking displacements which could modify the identity notion ruled by binary operations such as: contemporary vs popular. Besides Ferron´s research some personal experiences are mentioned. Those experiences helped, regarding methodology, to understand the main issues of the research from a practical perspective through the process of creation. The theoretical foundation of the thesis is supported by the notions of culture communicative mediations according to Jesús Martín Barbero, by the studies of Amálio Pinheiro about baroque and miscegenation, by the Helena Katz and Christine Greiner bodymedia theory and by the ecology of knowledge proposed by Boaventura de Souza Santos. This thesis aims to contribute with contemporary issues related to topics such as identity, body, creation and research